Cross-cultural adaptation of Chinese students in the United States: Acculturation strategies, sociocultural, psychological, and academic adaptation - Lai, Hongling; Wang, Dianjian; Ou, Xiancai (Frontiers in Psychology, 2023)
This study was conducted with the primary purpose to gain a comprehensive understanding of Chinese students’ acculturation by examining the effects of their acculturation strategies, sociocultural, psychological adaptation on the academic adaptation. The total number of 315 international Chinese students studying in the U.S participated in an online survey. The mid-point split method was used to classify the four acculturation strategies among Chinese students. The results of a Chi-square test, ANOVA analyses and hierarchical regressions reveal that separation was the most preferred acculturation strategy by the Chinese students while marginalization was the least desirable. Chinese students did the best in sociocultural adaptation but the worst in academic adaptation. However, students who achieved a good sociocultural adaptation encountered unexpected problems with their psychological adaptation. Findings also indicate that international Chinese students’ preference for separation and marginalization was associated with a better psychological and academic adaptation while integration and assimilation strategy was associated with a better sociocultural adaptation. Their academic adaptation can be predicted significantly by their psychological adaptation, not by their sociocultural adaptation.